Comparative efficacy of teriparatide and bisphosphonates or denosumab vs. teriparatide monotherapy in osteoporosis: a meta-analysis - Jin, Huan; Huang, Cai; Zhang, Yan; Dong, Ying; Xiong, Qi; Wang, Di; He, Ziyi; Shen, Lin; Ma, Chen; Wang, Zixian; Shuai, Bo (Frontiers in Pharmacology, 2025)
IntroductionTeriparatide (TPTD), a widely used bone-promoting drug in osteoporosis (OP) treatment, may cause compensatory bone resorption with long-term monotherapy (>6 months). Combining TPTD with anti-bone resorption drugs (e.g., bisphosphonates and denosumab) could reduce bone loss, yet existing randomised controlled trials (RCTs) remain inconclusive regarding their effects on bone mineral density (BMD) and bone turnover markers (BTMs). This study aimed to systematically evaluate the effect of TPTD combined with bisphosphonates or denosumab on BMD and fracture risk in OP patients, compared with TPTD monotherapy.MethodsPubMed, Embase, Cochrane Library, and Web of Science databases (until March 2025) were searched for RCTs comparing TPTD monotherapy with combination therapy. Primary outcomes included vertebral/non-vertebral fracture risk reduction and BMD changes (lumbar spine, femoral neck, hip); secondary outcomes covered BTM variations and adverse events.ResultsEight RCTs (n = 787) were meta-analysed using Review Manager 5.4. Results showed: ① No significant differences in vertebral (OR = 0.93, 95%CI 0.12–6.93) or non-vertebral fractures (OR = 0.68, 0.31–1.46) between groups. ② TPTD combined with denosumab significantly increased lumbar spine (+3.40%, 0.44–6.36), femoral neck (+4.00%, 1.96–6.04), and hip BMD (+4.25%, 3.20–5.29). Bisphosphonate combinations improved hip BMD in the short term (<24 months: +1.81%, 0.65–2.97) but not long-term (≥24 months).③ Combination therapies regulated BTMs bidirectionally: bisphosphonates suppressed P1NP (40%–80% reduction vs. monotherapy), while denosumab preserved OC levels (-8–16% vs. monotherapy).④ Safety profiles were comparable: hypercalcemia incidence (16.3% vs. 14.7%, OR = 1.22, 0.55–2.69), musculoskeletal pain (9.8% overall), with no osteonecrosis cases reported.ConclusionTPTD-denosumab combination is clinically preferable for BMD enhancement, though its long-term (>24 months) fracture risk reduction requires further validation.